Initial experience with transcatheter tricuspid valve repair in patients with cardiac amyloidosis - Hörbrand, Isabel; Volz, Martin J.; Siepen, Fabian aus dem; Aurich, Matthias; Schlegel, Philipp; Geis, Nicolas; Hegenbart, Ute; Konstandin, Mathias; Frey, Norbert; Raake, Philip (ESC heart failure, 2023)
Aims Wildtype transthyretin amyloid cardiomyopathy is an under-recognized cause of heart failure in elderly patients. Transcatheter tricuspid valve repair is a newly emerging therapeutic option for severe tricuspid regurgitation (TR). We present first insights into safety and possible benefits of this procedure in patients with cardiac amyloidosis. Methods and results Eight patients with cardiac non-hereditary (wildtype) transthyretin (ATTRwt) amyloidosis and severe to torrential TR, undergoing successful transcatheter tricuspid valve repair, were included in the analysis and compared to a control group of 21 patients without cardiac amyloidosis. All patients presented with an advanced stage of amyloid cardiomyopathy. Primary endpoint was reduction in TR at 3 months follow-up. Secondary endpoints were feasibility, safety, hospitalization or death, clinical improvement, cardiac biomarkers, and structural and functional right heart parameter obtained by echocardiography. Transcatheter tricuspid valve repair resulted in a significant reduction of TR (IV to II, P = 0.008) in all eight patients with cardiac amyloidosis (100%). Device success (amyloidosis 75% vs. control group 86%, P = 0.597) and overall probability of hospitalization or death (amyloidosis 13% vs. control group 25%, P = 0.646) were similar compared with those in the control group at 3 months follow-up. Transcatheter tricuspid valve repair led to an improvement of New York Heart Association functional class (P = 0.031) and 6 min walking distance (from 313 ± 118 to 337 ± 106, P = 0.012). TR reduction in amyloidosis patients was less extensive compared with that in control group (TR-reduction 1.6 ± 0.3, P = 0.008 vs. control group 2.3 ± 0.3, P < 0.0001). Furthermore, these patients showed no significant improvement of structural right heart parameters. Conclusions Transcatheter tricuspid valve repair is a safe and feasible new treatment option in patients with amyloid cardiomyopathy and has the potential to improve TR-grade and clinical status. However, the benefit appears to be less pronounced compared with patients without cardiac amyloidosis.